Three Concentric Tube Heat Exchange With NTU-Effective Method - Liyun Arun Hutagalung (Journal Basic Science and Technology, 2021)
Heat exchanger is an exchange device with three concentric pipe tubes with direct flow used to reduce hot fluid to cold fluid using cold water fluid. the research was carried out triple pipes that flowed in the same direction with 3 variationsin the temperature pipe of the hot water fluid th with a temperature of 50oC, 55oC and 60oC with temperature of cold water fluid tc 25oC and this study used a flow rate of 0.000025 m3/s = 0.000033 m3/s and 0.000041 m3/s.The results of this study showed that the equilibrium temperature obtained from the experimental results of the effectiveness of the one-way pipeline flow was 1 = 32.99% the effectiveness of thr second channel pipe of 2 = 66.48% and ont the effectiveness of the third channel pipe of 3 = 33.57% 3rd data with a debut of 0.000025 m3/s and the effectiveness of the opposite flow the channel one pipe is 1 = 55.16% on the effectiveness of the second channel pipe of 2 = 66.48% and on the effectiveness of the third channel pipe of 3 = 60.59% it is obtained in the with to 7 with a discharge of 0.000041 m3/s.